Flattened zero dispersion Photonic crystal fibers with embedded nano holes and ultra low confinement loss for supercontinuum generation - Fiaboe, K. F.; Kumar, P.; Roy, J. S. (Advanced Electromagnetics, 2019)
In this paper unique photonic crystal fiber (PCF) structure with nanoholes embedded have been studied. Embedded nanoholes have been filled with different materials of alcoholic groups like butanol, ethanol, methanol and propanol. Investigations of these structure shows flattened zero dispersion in visible range to far infrared regions. Simulated PCF structure reports ultra-low confinement loss of the order of 10-8 dB/km. Designed PCF promises to give large nonlinear coefficient of 3000 W-1Km-1 at 1335nm wavelengths. Numerical simulation of the fiber for the generation of supercontinuum generation (SCG) has been performed. Low power pump pulses of 50fs duration have been used. With a fiber of length of 15cm and pulses of 1kW, 2kW, 5kW and 10kW peak power, supercontinuum broadening of about 607nm, 908nm, 1987nm and 2405nm respectively.